A Note on In Vitro Regeneration of Balfour aralia (Polyscias balfouriana marginata L.) Shoots Using Shoot Tip Explants (University of Khartoum Journal of Agricultural Sciences, 2021)
The objective of this study was to investigate the effect of the cytokinins benzylaminopurine (BAP) and Kinetin on in vitro shootregeneration on shoot tips of Polyscias balfouriana marginata. Shoot tips were cultured on Murashige and Skooge (1962) medium (MS) supplemented with various concentrations of BAP and Kinetin at 0.0, 0.75, 1.5, 3, 6 mg/L for both. Results showed that Polyscias balfouriana marginata responded positively to growth regulators application and there was significantdifference among concentration treatments. The highest percentage of responded explants was given by BAP and Kinetin - free medium and the one containing the lowest concentration of both (0.75 mg/L). The concentration 3 mg/L BAP showed significantly the highest number of shoots/explant. There was no significant difference between kinetin concentratios 0.75 and 1.5mg/L, yet they resulted in significantlys higher number of shoots/explant compared to the control.The concentration 0.75 mg/L of both BAP and kinetin recorded the highest shoot length while the shortest shoot resulted from 6 mg/L of both cytokinins and the control of kinetin.